A manual of private investigation techniques : developing sophisticated investigative and business skills to meet modern challenges - Blake, William F. (Charles C Thomas, 2013)
This book will help the private investigator reevaluate business opportunities and identify goals for the future. The world of the private investigator is constantly changing due to the introduction of various legal requirements that have restricted or eliminated some of the methods available for obtaining information such as the various privacy protection acts. Additionally, most private investigators have restricted their business activities to a response mode; that is, conducting inquiries after an incident has occurred. Their preventive skills have been ignored to their financial detriment.